Integrating Local Wisdom for Economic Growth: A Career Development Model for Tourism Employees - Wardani, Aulia Nurlaili Kusuma; Maulana, Dede Yusuf; Ratnawati, Ratnawati; Arwin, Arwin; Sattar, Sattar (Yayasan Riset dan Pengembangan Intelektual, 2024)
The tourism industry plays a significant role in Indonesia's economy, particularly in regions with strong tourism potential. One notable cultural tourism destination in Jakarta is Kampung Betawi Setu Babakan, renowned for its unique Betawi cultural heritage. The area showcases diverse local wisdom, including Betawi architecture, cuisine, arts, and traditions, which hold considerable potential for integration into tourism development. Enhancing the career development of tourism employees at Kampung Betawi Setu Babakan is crucial to sustaining service quality and maintaining the destination’s appeal. This study aims to: (1) analyze current career development practices for tourism employees in Kampung Betawi Setu Babakan; (2) identify Betawi local wisdom that can be incorporated into employee career development; and (3) propose a career development model grounded in Betawi local wisdom. Employing a case study approach, data were collected through in-depth interviews, field observations, and document analysis. Findings reveal that career development practices in Kampung Betawi Setu Babakan remain suboptimal and lack integration of Betawi local wisdom. Key elements of Betawi culture, such as traditional architecture, culinary arts, and performing arts, were identified as potential resources for employee career development. The study formulates a career development model incorporating these cultural elements, featuring local wisdom-based training, culturally aligned career pathways, and a remuneration system that values contributions to cultural preservation. The proposed model offers managerial implications for improving service quality, enhancing destination competitiveness, and ensuring the sustainability of Betawi cultural heritage.